Genome-Wide Changes of Regulatory Non-Coding RNAs Reveal Pollen Development Initiated at Ecodormancy in Peach - Yu, Jiali; Bennett, Dennis; Dardick, Christopher; Zhebentyayeva, Tetyana; Abbott, Albert G.; Liu, Zongrang; Staton, Margaret E. (Frontiers in Molecular Biosciences, 2021)
Bud dormancy is under the regulation of complex mechanisms including genetic and epigenetic factors. To study the function of regulatory non-coding RNAs in winter dormancy release, we analyzed the small RNA and long non-coding RNA (lncRNA) expression from peach (Prunus persica) floral buds in endodormancy, ecodormancy and bud break stages. Small RNAs underwent a major shift in expression primarily between dormancy and flowering with specific pairs of microRNAs and their mRNA target genes undergoing coordinated differential expression. From endodormancy to ecodormancy, ppe-miR6285 was significantly upregulated while its target gene, an ASPARAGINE-RICH PROTEIN involved in the regulation of abscisic acid signaling, was downregulated. At ecodormancy, ppe-miR2275, a homolog of meiosis-specific miR2275 across angiosperms, was significantly upregulated, supporting microsporogenesis in anthers at a late stage of dormancy. The expression of 785 lncRNAs, unlike the overall expression pattern in the small RNAs, demonstrated distinctive expression signatures across all dormancy and flowering stages. We predicted that a subset of lncRNAs were targets of microRNAs and found 18 lncRNA/microRNA target pairs with both differentially expressed across time points. The genome-wide differential expression and network analysis of non-coding RNAs and mRNAs from the same tissues provide new candidate loci for dormancy regulation and suggest complex noncoding RNA interactions control transcriptional regulation across these key developmental time points.